2005
DOI: 10.1203/01.pdr.0000163386.32348.90
|View full text |Cite
|
Sign up to set email alerts
|

Relations of Body Fatness and Cardiovascular Fitness to Lipid Profile in Black and White Adolescents

Abstract: High body fatness is associated with unfavorable cardiovascular disease risk profiles in juveniles. However, the degree to which the deleterious effects attributed to fatness may actually be due to the low cardiovascular fitness (CVF) that is usually confounded with fatness is not known. This study determined in 14-to 18-y-old (n ϭ 398) youths the degree to which percentage body fat (%BF) and CVF explained variability in lipids and lipoproteins. Blood samples were taken after a 12-h fast. %BF was measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
25
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 15 publications
8
25
2
1
Order By: Relevance
“…We found that percent fat was highly correlated with each risk factor separately, in agreement with previous studies [1,6,11]. The influence of percent fat was also evident in the inverse correlations among fat and kgVO 2 max present in every age group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that percent fat was highly correlated with each risk factor separately, in agreement with previous studies [1,6,11]. The influence of percent fat was also evident in the inverse correlations among fat and kgVO 2 max present in every age group.…”
Section: Discussionsupporting
confidence: 92%
“…Which variable, fitness or fatness, is more important in determining CVD risk in youth is still controversial. Research has shown that a higher percent body fat is associated with increased CVD risk factors in youth, regardless of fitness levels [1,5,11]. Similarly, fatness has been associated with elevations in BP [1,4 -7,9], some blood lipids [1,4,6,11], and insulin [5][6][7].…”
mentioning
confidence: 99%
“…The results of our study are consistent with a small number of pediatric cross-sectional studies (4,15,16). We are not aware of any other longitudinal studies that have examined the effects of an increased waist circumference in childhood on CVD risk clustering in adolescence.…”
Section: Discussionsupporting
confidence: 90%
“…Esta observação é concordante com as de outros estudos mais recentes 19,[26][27][28] que reportam a existência de forte correlação entre a capacidade aeróbia e diversas medidas de avaliação da massa gorda em crianças e adolescentes, principalmente em sujeitos com %MG correspondentes aos grupos de risco (moderado e elevado).…”
Section: Discussionunclassified